Responsabilidade Social Empresarial: Obrigação e Voluntariedade Com estudo de Caso Projeto ELU Companhia Vale do Rio Doce em São Luís Maranhão - Martins, Paulo Haus (2008)
This study analyzes if it‟s adequate to limitate the concept of Corporate Social Responsibility only through voluntary initiatives, divested of any type of obligations. There are several and distinct concepts of Corporate Social Responsibility CSR (ASHLEY, 2000; WILLIAMS, 2007). It is usually understood as a social fact, an important movement leading to behavioral changes in corporate governance that has been occurring since the end of the 20th century, evidenced in this study (ASHLEY, 2000; WILLIAMS, 2007; URANI, 2005; TENÓRIO, 2004; GARCIA, 2004; PELIANO, 2003; MAIMON, 2005). Thus, the CSR concept matches the attempt to explain the phenomenon. The available literature has many citations about voluntary attitudes (PELIANO, 2003; MAIMON, 2005) and some authors restrict CSR to pure voluntarism, divested of any obligation (CHEIBUB e LOCKE, 2002). However, from our point of view, these concepts tend to contradict the legal nature of the responsibility concept itself, since it is always presumed to be linked to an obligation (LOPES, 2006; JONAS, 2006). In this study, we compare the concept of CSR to the concept of pure voluntarism that led us to the conclusion that it is inappropriate to conceive as responsibility something divested of obligations. We evaluated available literature about the concept of RSE, both international or Brazilian, and we categorized the concepts in kinship groups, subsequently commenting on them. We also studied legal sources regarding responsibility and social function, relating both to the field of sociology. Thus, we reached the conclusion that according to Brazilian law there is responsibility attributable to the companies that Law imputes to the distributive nature of private initiative, assigning them an obligatory dimension. Therefore, we conclude that it is inappropriate to conceive of CSR as pure voluntarism. This paper is accompanied by a case study of a Corporate Responsibility Project (CRP), presenting the context and evaluating the CSR concept presented in the study.